The impact of Distance learning during Coronavirus on the students’ motivation towards learning from the viewpoint of both teachers and parents, in Irbid Directorate, Jordan - Alhawari, Arwa Essa (Journal of Educational and Psychological Sciences, 2021)
This study aimed to understand the impact of Distance learning during Coronavirus on the students’ motivation towards learning from the viewpoint of both teachers and parents, in the Directorate of Irbid, Jordan. A descriptive survey approach was applied, which has been published via social media for the targeted sample of (221) A teacher, and (632) parents in Irbid directorate. The final results showed that the third axis has taken the lead with an average of 2.69, and a percentage of 58.2%, followed by the second axis with an average of 2.56 and a percentage of 47.97%, finally the first axis obtained an average of 2.94 with a percentage of 56.63%, which confirms that the availability of educational environment for distance learning greatly affects students’ motivation towards learning, and a bunch of recommendations has been proposed depending on the paper results, that can help in develop the distance education methods and enhance students’ motivation towards it. In Irbid Directorate, Jordan, and the majority of Arab countries.